S169 Sleep spindles and epilepsy. Issue 9 (September 2017) - Fabo, Daniel
Abstract : Sleep spindles (SSPs) are well known EEG phenomena characteristic to slow wave sleep (SWS). It has been demonstrated that SSPs participate in memory consolidation process during sleep. There are evidences of the participation of SSPs in various types of epilepsy ranging from idiopathic generalized to focal ones. Here we report the results of our investigation in human focal epilepsy patients implanted with cortical and thalamic macro-, and microelectrodes. Intracortical generators of SSPs in humans were explored and participation of different thalamic output systems was hypothesized. We review the human thalamic recordings and the participation of different thalamic nuclei in sleep spindling. We report our results from anterior nucleus of thalamus in temporal lobe epilepsy patients. We draw conclusions about the altered role of SSPs in the epileptogenic process.